Impact of education on antibiotic literacy and awareness among pharmacy students at a Japanese university: a questionnaire survey - Masayuki Maeda; Kozue Yamaguchi (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Considering the global threat of antimicrobial resistance (AMR), Japan implemented a national action plan in 2016 that emphasized antibiotic education for healthcare professionals. However, pharmacy education in Japan lacks comprehensive antimicrobial stewardship (AMS) content, leading to insufficient antibiotic awareness and literacy among graduates. This study aimed to assess and improve antibiotic literacy and awareness among undergraduate pharmacy students at Showa University. Methods Students who were admitted in 2015 were given a 90-min lecture on AMS, covering acute upper respiratory infections, before their fifth-year clinical training in 2019. The lecture was delivered by a certified pharmacist in infection control. A paper-based, anonymous self-administered questionnaire survey on antibiotic knowledge and literacy was distributed to first- and fifth-year students in 2019 and fifth-year students in 2023. The questions in the survey were based on the Antibiotics Awareness Survey 2018. Results The survey results showed an 82–99% response rate among first- and fifth-year pharmacy students in 2019 and 2023. Although two-thirds of first-year pharmacy students lacked antibiotic knowledge, most fifth-year students had appropriate knowledge. Moreover, fifth-year students had a proper understanding of bacterial infections and antibiotic identification, which improved after clinical training and additional lectures. The percentage of students who would stop using antibiotics when they felt better dropped from 39% among first-year students to 21% among fifth-year students. Fifth-year students were more likely to dispose of leftover antibiotics and less likely to keep them than first-year students. Over 80% of students provided antibiotic counseling primarily for common cold treatments during clinical training. Conclusions The survey results highlighted gaps in antibiotic awareness among Japanese pharmacy students and demonstrated the positive impact of education. This study emphasizes the need for an antibiotic literacy curriculum, especially for viral respiratory infections, to support efforts in curbing AMR. Moreover, policymakers should develop policies for developing and securing faculty that are knowledgeable in clinical infectious diseases across Japanese pharmacy schools.